(3GdehGLgI GdJTQjYjI dLQGFe Shb GdeGd aj GdJTQjY GdeUQj (B/ s - (3CMeO jMji SYO RZdhd s; (3TQja SjO cGeds; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2015)
(3JYJHQ GdCShGb GdeGdjI EMOi Cge GdbWGYGJ GdGbJUGOjI aj cd GdOhd, hJcJSH CgejJgG ef GdOhQ Gdege GdPj Jbhe Hg agj GdeLGd GdWHjYj hGdBef dJOGhd GdKQhGJ hJfejJgG ef NdGd TQGA hHjY GdChQGb GdeGdjI, hdPdc abO bSe GdHGMK GdaUd GdJegjOj Edi CQHYI eHGMK, GdChd dYQV eGgjI HhQUI GdChQGb GdeGdjI, hJfGhd GdeHMK GdKGfj GdJfXjeGf GdJTQjYj hGdEOGQj ddHhQUI, hJfGhd GdeHMK GdKGdK GdeUGdM eMd GdMeGjI GdbGfhfjI, CeG GdeHMK GdQGHY abO JfGhd GdMeGjI GdbGfhfjI dHhQUI GdChQGb GdeGdjI(B. (3hdbO fU GdeTQYGf GdeUQj hGdCeQjcj aj bhGfjf CShGb GdChQGb GdeGdjI Ydi GdCaYGd GdJj JgOO GdeUGdM GdeYJHQI hGdMbhb GdhGLH MeGjJgG HgOa UjGfI GdHhQUI cbWGY ef Cge bWGYGJ GdGbJUGO, MjK JONd GdeTQY aj cdG GdHdOjf HJLQje gPg GdCaYGd hCaQOG MeGjI LfGFjI dgG, hfXkQG dJYOO UhQ LQGFe Shb GdChQGb GdeGdjI aj GdJTQjYjf GdeUQj hGdCeQjcj, hdbO CaQOfG dPdc GdHGH GdChd GdPj JfGhd UhQ LQGFe GdHhQUI aj GdJTQjY GdeUQj hGdbGfhf GdebGQf ef NdGd KdGKI aUhd, JfGhd GdChd LQGFe eeGQSI GdfTGW HGdeNGdaI dbGfhf Shb QCS GdeGd, hJfGhd GdKGfj LQGFe GdJRhjQ hGdZT aj fWGb Shb QCS GdeGd, hGdKGdK JfGhd LQGFe GdENdGd HGdQbGHI GdeaQhVI Ydi Shb QCS GdeGd(B. (3Ke bGe GdHGMK HEdbGA GdVhA Ydi GdLhGfH GdELQGFjI GdNGUI HLQGFe Shb QCS GdeGd aj GdJTQjYjf GdeUQj hGdCeQjcj MjK CaQOG bhGYO NGUI HLQGFe Shb GdChQGb GdeGdjI cj JJfGSH eY eG JJejR Hg ef JYbjO aj hSGFdgG hJWhQ aj CfeGWgG hUYhHI aj EKHGJgG NQhkLG Yf GdbhGYO GdYGeI ddbGfhf GdELQGFj MjK bQQG dgG bbjb Ch aj eQMdI GdeMGceI, deOi PGJjI bhGYO GdeMGceI aj LQGFe Shb QCS GdeGd s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2015s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B389-414s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdJTQjY GdeUQj s; (3GdehGLgI GdJTQjYjI s; (3Shb GdeGd s; (3HhQUI GdChQGb GdeGdjIs; (3GdLgGR GdEOGQj dShb QGS GdeGds; (3GdMeGjI GdLfGFjI dGShGb QGS GdeGds; (3UhQ LQGFe GdHhQUgs; (3LQjeg WQM GdChQGb GdeGdjI HGdeNGdaI ddbGfhfs; (3LQjeg GdJUQa aj GdChQGb GdeGdjIs; (3LQjeg eNGdaI GddGFMI GdJfajPjIs; (3LQGFe GdJRhjQaj SLdGJ GdTQcIs; (3eGgjI GdJYGhf GdOhdjs; (3LQjeI hba GdfTGWs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs